Breakthrough : how one teen innovator is changing the world - Andraka, Jack. 1997- (Harper, an imprint of HarperCollinsPublishers, 2015)
"Teen scientist Jack Andraka chronicles his development of an inexpensive early detection test for pancreatic, ovarian, and lung cancer, and recounts his own personal story of overcoming depression and homophobic bullying. Includes hands-on science experiments"--Publisher.